A Soldier’s Preparation for Second Innings – A Review - Ms. Pallavi Chopade, Prof. Kirti S. Gupta (International Journal of Advanced Science and Technology, 2020)
Defence personnel are a unique population that are disciplined, dedicated and devoted to duty and are well trained to cope in difficult situations so as to retain the young profile of defense forces. In their later life, they are forced into career transition once their serving term is over. Career transition is a very important phase in the life of an individual. Researchers are realizing the importance of this and are investigating into the various aspects of career transition today.